Psychological stress‐induced cerebrovascular dysfunction: the role of metabolic syndrome and exercise. Issue 5 (25th March 2018) - Brooks, Steven; Brnayan, Kayla W.; DeVallance, Evan; Skinner, Roy; Lemaster, Kent; Sheets, J. Whitney; Pitzer, Christopher R.; Asano, Shinichi; Bryner, Randall W.; Olfert, I. Mark; Frisbee, Jefferson C.; Chantler, Paul D.
Abstract : New Findings: What is the central question of this study ? How does chronic stress impact cerebrovascular function and does metabolic syndrome accelerate the cerebrovascular adaptations to stress? What role does exercise training have in preventing cerebrovascular changes to stress and metabolic syndrome? What is the main finding and its importance ? Stressful conditions lead to pathological adaptations of the cerebrovasculature via an oxidative nitric oxide pathway, and the presence of metabolic syndrome produces a greater susceptibility to stress‐induced cerebrovascular dysfunction. The results also provide insight into the mechanisms that may contribute to the influence of stress and the role of exercise in preventing the negative actions of stress on cerebrovascular function and structure. Abstract: Chronic unresolvable stress leads to the development of depression and cardiovascular disease. There is a high prevalence of depression with the metabolic syndrome (MetS), but to what extent the MetS concurrent with psychological stress affects cerebrovascular function is unknown. We investigated the differential effect of MetS on cerebrovascular structure/function in rats (16–17 weeks old) following 8 weeks of unpredictable chronic mild stress (UCMS) and whether exercise training could limit any cerebrovascular dysfunction. In healthy lean Zucker rats (LZR), UCMS decreased (28%, P  < 0.05) ex vivo middle cerebral artery (MCA) endothelium‐dependent dilatation (EDD), but changes in MCA remodelling and stiffness were not evident, though cerebral microvessel density (MVD) decreased (30%, P  < 0.05). The presence of UCMS and MetS (obese Zucker rats; OZR) decreased MCA EDD (35%, P  < 0.05) and dilatation to sodium nitroprusside (20%, P  < 0.05), while MCA stiffness increased and cerebral MVD decreased (31%, P  < 0.05), which were linked to reduced nitric oxide and increased oxidative levels. Aerobic exercise prevented UCMS impairments in MCA function and MVD in LZR, and partly restored MCA function, stiffness and MVD in OZR. Our data suggest that the benefits of exercise with UCMS were due to a reduction in oxidative stress and increased production of nitric oxide in the cerebral vessels. In conclusion, UCMS significantly impaired MCA structure and function, but the effects of UCMS were more substantial in OZR vs . LZR. Importantly, aerobic exercise when combined with UCMS prevented the MCA dysfunction through subtle shifts in nitric oxide and oxidative stress in the cerebral microvasculature. Abstract :